IMPLEMENTASI PERANCANGAN PERANGKAT LUNAK UNTUK KENDALI DAN MONITORING MESIN VACUUM FORMING OTOMATIS - Ridlwan, Hasvienda M.; Prasetya, Sonki; MumpuniAdhi, Pribadi; Muslimin, Muslimin; Mulyono, Sugeng (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
Implementation of software design for vacuum forming machines is the focus of this paper. This vacuum forming machine will be used for small and medium industries (IKM) in food in Indonesia, where the packaging process is essential. Packaging materials in the food business are polystyrene plastic (PS) and polyvinyl chloride (PVC), which are generally sold freely in specific sizes. The problem that arises in SMEs is the packaging that does not fit, both the size and shape of the product. On the other hand, small-scale packaging machines are still quite expensive in terms of cost because the machines do not originate domestically. Therefore, an IKM scale Vacuum Forming machine with economical costs is needed for the IKM business. Testing software for vacuum forming machines has been running using Labview and Arduino by utilizing serial USB communication with NI-Visa. The experimental results of the designed system have been successfully implemented to the sensors and actuators via the Arduino Uno, indicating that temperature control can stabilize the heat after 3 minutes of heating. Meanwhile, the software that has been designed has been successfully implemented on LabView can monitor and help operators to use the machine easily.